The sex ration in a dioecious endemic plant, Silene diclinis - Prentice, H. C. ; 0000-0003-2548-0525 (Genetica, 1984)
Silene diclinis is a rare Spanish relative of the well-studied dioecious S. dioica and S. latifolia (=S. alba, S. pratensis). The main wild population and its cultivated derivatives showed female biased sex ratios. The ratios did not differ significantly between subpopulations or between the wild and cultivated samples, but they did deviate significantly from the expectation of a 1:1 male to female ratio. The characteristically biased sex ratio may be an incidental property of the XY sex determination system, with X-containing (female determining) pollen competing more effectively on the style than Y-containing grains.
Copyright: Copyright 2007 Elsevier B.V., All rights reserved.